Diversidade de anfíbios em diferentes estágios de conservação da mata ciliar em uma região de floresta subtropical no sul do Brasil - Almeida, Priscila Cassiano de (2019)
Discern as human activities impact amphibians and understanding the negative impacts of anthropization are among the main challenges to soften the natural population's decline. The comprehension of the effects of the reduction and fragmentation of the environment are fundamentals for proposing more effective conservation actions. The objective of this study was to identify how the diversity of Anurans Amphibians varies in different stages of conservation of riparian forest in a subtropical region of southern Brazil. The hypothesis was that the more conserved the riparian forest, the greater the diversity and the presence of highly selective species in relation to habitat use. This study was developed in the Fritz Plaumann State Park (PEFP), located in the countryside of Concórdia (SC). For collection were chosen four sampling areas, representing different stages of conservation: two areas in the around and two areas within the PEFP. The samplings occurred from November 2017 to April 2018. Linear transects of 100 meters long were established within each area, covered from twilight to 24:00 hours. To evaluate the stage of streams conservation was applied the Rapid Assessment Protocol (PAR) of habitat biodiversity and river basin sections. For the richness estimation and determination of sample sufficiency size were used the richness estimators Jack 1 and Chao 1. The comparisons between the areas for richness and number of individuals were made through analysis of variance (ANOVA) and Tukey Test. To compare the similarity between the areas, the Jaccard’s coefficient (SJij) was used. The diversity between areas was compared using the Shannon H' Index. Ten species of Anurans were recorded, distributed in 7 families. The PAR score was lower in the around’s areas the PEFP and higher in the areas within the PEFP. The surrounding areas had scores equivalent to altered environments, while the areas within PEFP had scores equivalent to natural environments. There was a significant difference in the number of species recorded in and around the PEFP. The species diversity was significantly higher in the areas within the PEFP than in the surrounding. The composition of species varied between areas. Only two species occurred simultaneously in and around the PEFP, showing low similarity. The set of results indicates that the richness, diversity, and composition of Anuran amphibians vary according to the degree of riparian forests conservation. Anuran amphibians were sensitive to variations in areas of streams environments. The conserved environments promoted greater diversity and maintenance the species of selective Anurans. Riparian forests with smaller width or with impacts of agriculture use are occupied by less selective species and with greater ecological amplitude.